Differences of the stem vascular system across populations of two tropical species under contrasting water conditions - Blagitz, Marcela; Nogueira, Anselmo; Marcati, Carmen Regina [UNESP] (Brill Academic Publishers, 2021)
Structural differences in the secondary vascular tissues among habitats can contribute to understanding species performances, especially regarding water and photosynthate transport. The pattern of association between the secondary xylem tissue and water availability from the environment has been widely studied, unlike the secondary phloem, which has been barely explored. Here, we evaluated the structural variation of the secondary xylem and phloem in stems of four populations of two tropical tree species under contrasting water conditions. We also investigated the mirrored structure between both tissues. At dry sites, Moquiniastrum polymorphum had higher vessel density, thicker xylem fibers cell walls, and taller rays in both tissues commonly associated with safe transport, in agreement with our expectations. In contrast, the populations of Zanthoxylum rhoifolium had most features in disagreement with the water availability of each site. The perforation and sieve plates, the ray composition, and the axial parenchyma were similar in the two tree species' xylem and phloem tissues. However, the quantitative descriptors of cell sizes were not correlated between the xylem and phloem. In general, there is a different pattern of morphological variation across sites in the two tropical tree species, highlighting that any generalization regarding the vascular system structure across environments should be avoided. Xylem and phloem revealed a mirrored structure in a few qualitative features, not followed by the dimensions of different cell types. Future research needs to explore the causes of the unexpected structural variation in the vascular system across populations in tropical tree species.
Keywords: Asteraceae; Atlantic rain forest; Cerrado; Moquiniastrum polymorphum; Rutaceae; Secondary phloem; Secondary xylem; Zanthoxylum rhoifolium